The use of Nb in rapid solidified Al alloys and composites - Audebert, Fernando Enrique (2013)
The worldwide requirements for reducing the energy consumption and pollution have increased the demand of new and high performance lightweight materials. The development of nanostructured Al-based alloys and composites is a key direction towards solving this demand. High energy prices and decreased availability of some alloying elements open up the opportunity to use non-conventional elements in Al alloys and composites. In this work the application of Nb in rapid solidified Al-based alloys and Al alloys matrix composites is reviewed. New results that clarify the effect of Nb on rapid solidified Al alloys and composites are also presented. It is observed that Nb stabilises the icosahedral Al–Fe/Cr clusters, enhances the glass forming ability and shifts the icosahedral phase decomposition towards higher temperatures. Nb provides higher corrosion resistance with respect to the pure Al and Al–Fe–RE (RE: rare earth) alloys in the amorphous and crystalline states. The use of Nb as a reinforcement to produce new Al alloy matrix composites is explored. It is observed that Nb provides higher strength, ductility and toughness to the nanoquasicrystalline matrix composite. Nb appears as a new key element that can improve several properties in rapid solidified Al alloys and composites.